2006
DOI: 10.3182/20060329-3-au-2901.00030
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Instrumental Variable Approach for Identifying Hybrid Continuous-Time Box-Jenkins Models

Abstract: The paper describes and evaluates an optimal instrumental variable method for identifying hybrid continuous-time transfer function models of the Box-Jenkins form from discrete-time sampled data, where the relationship between the measured input and output is a continuous-time transfer function, while the noise is represented as a discrete-time AR or ARMA process. The performance of the proposed hybrid parameter estimation scheme is evaluated by Monte Carlo simulation analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Indeed, the results obtained here and in other studies we have carried out, suggest that SRIVC provides an excellent default algorithm for day-to-day applications of this kind. Of course, as illustrated in other simulation studies reported by Young et al (2006), the advantages of full RIVC estimation can be significant in the case of more severely coloured noise, particularly when the AR model has roots near to the unit circle. For example, the results shown in Table 1 were obtained by MCS analysis using a simulation model based on the SRIVC estimated parameters but with the noise process simulated as a first order AR process with denominator polynomial C(z −1 ) = 1 − 0.96z…”
Section: Full Rivc Estimationmentioning
confidence: 94%
See 3 more Smart Citations
“…Indeed, the results obtained here and in other studies we have carried out, suggest that SRIVC provides an excellent default algorithm for day-to-day applications of this kind. Of course, as illustrated in other simulation studies reported by Young et al (2006), the advantages of full RIVC estimation can be significant in the case of more severely coloured noise, particularly when the AR model has roots near to the unit circle. For example, the results shown in Table 1 were obtained by MCS analysis using a simulation model based on the SRIVC estimated parameters but with the noise process simulated as a first order AR process with denominator polynomial C(z −1 ) = 1 − 0.96z…”
Section: Full Rivc Estimationmentioning
confidence: 94%
“…This more sophisticated and statistically motivated RIVC method of CT identification and estimation is described and evaluated in Young et al (2006) in order to demonstrate the advantages of the stochastic model formulation. This evaluation is based on comprehensive Monte Carlo Simulation (MCS) analysis.…”
Section: Optimal IV Methods For Ct Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various methods can be applied to the transformer model estimation problem [16]. However, only the most reliable method, denoted the simplified refined instrumental variable method for continuous-time system identification (SRIVC) [17], is chosen here. Let the continuous-time model of the actual system be…”
Section: A Direct Continuous-time Model Identificationmentioning
confidence: 99%